As diretrizes curriculares nacionais na formação inicial em educação física: realidade e possibilidades - Welter, Janaíne (2017)
Keywords: This study aims to analyze the initial training from the National Curriculum Guidelines of Physical Education and its possibilities presented by the training proposals of the Licenciatura de caráter Ampliado e Minuta de Projeto de Resolução (2015). It is a research that adopts a critical position, having as theoretical side the dialectical historical materialism. The collection of information was based on the documentary analysis, based on the methodological categories of historicity, totality, contradiction, mediation, praxis and in the content categories: Physical Education; Initial training and educational policies. The DCNEF of 2004 presents as characteristics the need to develop skills and abilities, a conception of Physical Education as health promoter, fragmentation of knowledge that culminates in the dichotomy Degree and Bachelor. The Licenciatura de caráter Ampliado is a proposal of formation, based on historicity and praxis as a scientific matrix, showing that there are possibilities of overcoming a unilateral formation linked to the capitalist mode of production. It was found that the Minuta de Projeto de Resolução (2015) resents many characteristics of the Resolução 07/2004 and presents a succinct advance when proposing the unification for the courses of Physical Education. It can be seen that based on the three proposals of initial formation in Physical Education listed – DCNEF de 2004, Licenciatura de caráter Ampliado e Proposta de Minuta de Resolução (2015) – there is only a possibility of formation that is resistant to the advances of the capitalist system, the proposal form the Licenciatura de caráter Ampliado.